2023
DOI: 10.1002/ird.2820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and nitrogen fertilizer management on wheat grain baking quality based on the SiriusQuality2 crop model

Abstract: The baking quality of wheat grain is significantly affected by irrigation and nitrogen fertilizer management. This study aimed to model the impacts of nitrogen and water stress on winter wheat grain protein composition using SiriusQuality2. SiriusQuality2 was calibrated by using sufficient nitrogen and water treatments and used to evaluate 16 treatments in semi‐arid regions. Then, simulated baking quality and yield over a past 51‐year period were used to screen and optimize the selected 203 management practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Previous reports also found that nitrogen application could influence the effect of irrigation on protein content; for example, irrigation in the range of 0-225 mm had a diluting effect on grain quality, while protein content and wet gluten content were decreased with increasing irrigation, and this effect could be diminished by nitrogen application [31]. Moderately high nitrogen fertilisation under water deficit conditions not only alleviated losses of grain yield caused by water deficit, but also increased protein accumulation [15,48]. Our current work showed that high nitrogen fertilisation significantly increased GSP content under no irrigation conditions in HF conditions, but it decreased significantly under two irrigation steps.…”
Section: Irrigation and Nitrogen Significantly Affect Gsp Content And...mentioning
confidence: 94%
“…Previous reports also found that nitrogen application could influence the effect of irrigation on protein content; for example, irrigation in the range of 0-225 mm had a diluting effect on grain quality, while protein content and wet gluten content were decreased with increasing irrigation, and this effect could be diminished by nitrogen application [31]. Moderately high nitrogen fertilisation under water deficit conditions not only alleviated losses of grain yield caused by water deficit, but also increased protein accumulation [15,48]. Our current work showed that high nitrogen fertilisation significantly increased GSP content under no irrigation conditions in HF conditions, but it decreased significantly under two irrigation steps.…”
Section: Irrigation and Nitrogen Significantly Affect Gsp Content And...mentioning
confidence: 94%